The matching approach on expenditure patterns of migrant households: evidence from Moldova - Robert Poppe (Kiel Institute for the World Economy (IfW), 2007)
This paper examines the effect of temporary and permanent migration on household expenditures and on asset/durables ownership. Using household survey data from Moldova, this paper relies on the matching approach for identification. It is shown that temporary migrant households have additional expenditures for food compared to non-migrant households. Further, non-migrant and temporary migrant households have higher expenditures for the repayment of loans than permanent migrant households. Concerning the ownership of goods or assets in 2006 compared to the regional crisis in 1998, temporary migrant households are more likely to own more assets or goods than non-migrant households. Overall, the findings indicate that temporary migration has a stronger effect on household expenditures than permanent migration.
Keywords: 330; expenditures; remittances; migration; matching; Migranten; Internationale Arbeitsmobilität; Saisonarbeitskräfte; Verbraucherausgaben; Rücküberweisung (Migranten); Dauerhaftes Konsumgut; Moldawien